An in vitro investigation of the survival and/or growth of Campylobacter jejuni in broiler digestate from different feed types. (13th October 2020) - Greene, G.; Koolman, L.; Whyte, P.; Lynch, H.; Coffey, A.; Lucey, B.; Egan, J.; O'Connor, L.; Bolton, D.
Abstract: Campylobacter spp. is the leading cause of bacterial gastroenteritis worldwide and poultry are the primary reservoir. The aim of this study was to investigate the survival and/or growth of Campylobacter jejuni NCTC 11168 in broiler digestate prepared from commercial starter, grower and finisher feed formulations. Bolton broth and digestates were prepared, inoculated with C. jejuni NCTC 11168 (approximately 3 log10 CFU per ml) and incubated under microaerobic conditions at 42°C for 24 h. Samples were taken at t = 0 (immediately after inoculation) and every 3 h thereafter, serially diluted and plated onto mCCDA. Campylobacter jejuni grew as expected in Bolton broth (control) reaching the early stationary phase after approximately 15 h. In contrast, although bacterial concentrations were maintained for at least 9 h, none of the feed digestates supported the growth of C. jejuni, which were not detected after 15 h. It is suggested that the nutrients available in the feed digestates are not enough to support C. jejuni growth and that additional factors may be at play in the avian gastrointestinal tract. Abstract : Significance and Impact of the Study: This study investigated the survival and/or growth of Campylobacter jejuni NCTC 11168 in broiler digestate prepared from commercial starter, grower and finisher feed formulations. The inability of this bacteria to survive and/or grow suggests that factors other than the release of nutrients in the broiler digestive system are involved in promoting Campylobacter colonization. This finding combined with previous observed growth in irradiated caecal contents is consistent with evidence suggesting the preferential colonization of the lower avian gut by Campylobacter and the suggestion that the bacterial microbiome and the nutrients it produces play a critical role in this process.